ANALISIS TINDAKAN ILOKUSIONER DALAM DIALOG JAMES DAN ANGELA DI SILENT HILL 2 - Ilahi, Ruhul Justice; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2026)
This study analyzes the use of illocutionary acts in the dialogues of James Sunderland and Angela Orosco in Silent Hill 2 Remake (2024). Drawing on Speech Act Theory, as proposed by Austin (1962) and classified by Searle (1979), this research aims to identify the types of illocutionary acts and to examine how dominant acts represent each character. Using a descriptive qualitative method with qualitative content analysis, the data consist of dialogues from five encounter scenes collected through gameplay recording and transcription. The findings reveal four illocutionary acts: representatives, directives, expressives, and commissives, while declaratives are absent. James’s dialogue is dominated by representative acts (42.6%), followed by directive (29.4%), expressive (22.1%), and commissive (5.9%) acts, portraying him as reflective and psychologically conflicted in his attempts to rationalize his situation. In contrast, Angela’s dialogue is strongly dominated by representative acts (53.0%), followed by directive (26.5%), expressive (16.9%), and commissive (3.6%) acts, portraying her as traumatized and defensive through her assertions of trauma-related beliefs and self-blame. Future research may employ a psycho-pragmatic approach to deepen character analysis. Keywords: Illocutionary Acts, Speech Acts, Video Game, Video Game Dialogue, Pragmatics